How efficient is Malaysia’s secondary education? (Bagaimanakah keberkesanan pendidikan menengah di Malaysia) - Mohd Arshad, Mohd Nahar (Universiti Kebangsaan Malaysia, 2013)
The purpose of this study is to investigate the level of technical efficiency of Malaysia’s secondary education in comparison with other countries. Education efficiency has become an important issue given the pressing levels of public deficit and debt of many countries. Since the educational sector always receives high priority in budget allocations, an evaluation of whether the allocations made for education has been technically efficient is important. With budget constraints and high expectation by the public to see a continuous improvement in students’ academic achievement, the educational sector has been put under pressure to deliver. The study employs TIMSS 2007 data, involving 44 countries. The technique used to calculate the level of technical efficiency is Data Envelopment Analysis (DEA). Malaysia is found technically inefficient in terms of utilising its educational resources to achieve better TIMSS results in comparison with the other countries. Even after controlling for the environmental variable, Malaysia’s secondary education remains technically inefficient.